DIFFUSION OF “LELANG SYSTEM” AND FARMER CHOICE ON IRRIGATION WATER MANAGEMENT MODEL - mohammad rondhi; yasuhiro mori; takumi kondo (UPT Penerbitan Universitas Jember, 2017)
In Indonesia irrigation water management in tertially canal is otonomusly organized by water usage assosicition (WUA). The management varies among areas and periods. In Klambu Wilalung irrigation area last four decades some WUAs has experienced some managements change, that are ulu-ulu system within 1980s, dharma tirta system within 1990s, “P3Aswakelola system” in 1990s-now, and recently “P3A-lelang system” that has first time being apllied since 2005. Nowdays the two latter systems are most applied systems in the area. The lelang system means WUA as water supplier has to provide some budget in advance in order to get a right in water management. This might have more benefit to farmer. However, the spreading of lelang system in the area is still unidentified. The aims of the research are (1) to know the spreading of the “lelang system” (2) to understand main factor of farmer choice in water management system, (3) to know correlation of area, contract period, and productivity to value of lelang. This research is conducted by cencus to 34 WUA in Klambu Wilalung irrigation area, Kedung Ombo dam, Central Java. This data is analysed by descriptive quantitaive method by Pearson corellation. The results show that from the WUA 67% is apllying lelang system and the rest applying swakelola system. The main reason applying lelang system is the budget availability to establish agriculture infrastructure (including irrigation infrastructure) in the initial period of geverning WUA. Then, reason applying swakelola system is the system accentuate working together (gotong royong) in managing irrigation water. Furthermore, area has positive and significant correllation to value of lelang, while contract duration and productivity don’t have correlation to value of lelang. This research also find that some WUAs that applied contract system change to swakelola system. This research conclude that farmer choice to water irrigation system is depend on good governance of WUA.